CONCEPTS OF A SYNERGISTIC APPROACH TO THE FORMATION OF A SECURITY-ORIENTED INFORMATION ENVIRONMENT IN UKRAINE - ONYSHCHENKO, Svitlana; BILKO, Stanislav (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the issues of forming a security-oriented information environment in Ukraine. In the context of increasing influence of internal and external destabilizing factors, realization of unprecedented threats to all components of national security caused by the military aggression of the Russian Federation, ensuring the formation of a security-oriented information environment is the basis for the realization of national interests, which creates new opportunities for strengthening the security of the national economy. The methodological content of the concepts of scientific approaches to ensuring the security of the national economy is investigated. It is proved that the information security of Ukraine's economy is a complex, non-equilibrium, non-linear, self-organizing system, which justifies the use of a synergistic approach in its research. The concepts of forming a security-oriented information environment substantiated in the study are based on the provisions of a new paradigm of using the opportunities associated with the development of information technology and preventing and countering new threats to information security by protecting information, ensuring the reliability, integrity and availability of public information resources, restricted information, in particular, the one circulating in the economic information infrastructure facilities and determining the further secure development of the state by creating a security system for computer systems for economic data processing (CSEDP) and taking into account external and internal threats realized as a result of the military aggression of the russian federation. The authors have developed a model for the formation of a security-oriented information environment in Ukraine aimed at protecting national economic interests and ensuring the security of the national economy. These key conceptual provisions should serve as a theoretical basis for further development of the methodology for ensuring information security of the national economy.
Keywords: security-oriented information environment; information security; concepts; synergistic approach; national economy